Social Media Trends in Arabic Language Learning at the University of Muhammadiyah Malang and KH. Abdul Chalim - M. Ainur Roziqi; Abdul Haris; Alfa Naja Imamuna (LISANIA: Journal of Arabic Education and Literature, 2026)
This study aims to compare social media use trends, student characteristics, and the supporting and inhibiting factors in Arabic language learning at Universitas Muhammadiyah Malang (UMM) and Universitas Abdul Chalim (UAC) Mojokerto. A mixed-methods approach with a Parallel Convergent Design was employed, in which quantitative and qualitative data were collected and analyzed simultaneously but separately. Quantitative data were obtained through questionnaires administered to 80 students, while qualitative data were gathered through interviews with 10 informants. The findings revealed that students at both universities primarily used YouTube and WhatsApp as the main platforms for Arabic language learning. Students at UMM tended to focus on searching for learning materials and developing independent learning, whereas students at UAC more intensively utilized WhatsApp as a collaborative medium for completing academic assignments, reflecting the collective culture of the pesantren-based environment. Furthermore, the major challenge identified in both institutions was the high level of non-academic social media use, which often distracted students from learning activities. The findings also indicate that differences in institutional culture influence students’ preferences and patterns of social media use in the learning process. These findings provide important implications for the development of digital-based Arabic language learning curricula and instructional models that are more adaptive to local social and cultural contexts.